Chilean Exports of Copper to Wales During the Nineteenth Century: Its Impact on the Chilean and Welsh Economies - Llorca-Jaña, Manuel (Revista de Historia Social y de las Mentalidades, 2017)
The purpose of this paper is to bring more statistical precision to assess the impact of chilean copper exports to Wales on both the chilean and the welsh economies during the nineteenth century. Despite the previous and important contributions of other scholars, there were still some blurred areas which called for clarification. My main conclusions are: c.1800-1830s, the welsh copper connection was unimportant for the chilean economy; during the 1840s-1870s, although wales was not an important market for chilean copper bars, the welsh connection was quite important for the chilean copper industry as a whole, and for the entire chilean economy too; during the 1880s-1890s this importance declined importantly. Regarding the relative importance of Chile for the welsh copper industry, although Chile was an important supplier of copper ores for wales, Cuba was more important during the 1840s-1850s. In the 1860s Chile was the top ore supplier for the welsh market, but there was a greater diversity in supply, with little dependence on chile. Likewise, Chile became far less important during the 1870s-1890s as supplier of ores for Wales. As far as regulus is concerned, welsh copper refiners relied heavily on chilean regulus during the 1850s-1870s, but this position was taken by spain and the usa during the 1880s-1890s.
Keywords: Copper; Chilean Exports; Nineteenth Century; Wales